Certain Aspects of the Interbranch Regulation of the Convictіs’ Labor Organization in France - KRYMOV, Aleksandr Aleksandrovich; RODIONOV, Alexey Vladimirovich; SKIBA, Andrey Petrovich (Journal of Advanced Research in Law and Economics, 2017)
The article analyzes some aspects of the French legislation, which concern the regulation of convicts’ labor organization and penitentiary as a whole (taking into account some of the provisions of Russian, American, German and British criminal, penal and criminal procedural law). The legal acts, which regulate the organization of convicts’ labor in France were determined. During the research the features of the regime of semi-freedom and labor organization of convicts, sentenced to punishments that are not related with incarceration were studied. The work is based on the use of comparative legal and historical research methods. As information base of the research were used acting French regulations that govern the execution of criminal penalties, as well as legal acts, concerning penitentiary special contingent’s labor organization. Was also used data from the French state statistics in the field of execution of criminal punishments. The cross-country comparisons with regard to the relevant rules and regulations of the laws of Russian Federation, the Federal Republic of Germany and the United States were carried out.